Status of out of law persons - Šerėnas, Algirdas (Genocidas ir rezistencija, 1997)
The whole of society in the emerging and developed socialist Soviet empire was divided according to its harmfulness and harmlessness into several public and non–public categories: the free, the prisoners, the specially detained, etc. Each category was divided into groups, and groups into subgroups, etc. The categories of prisoners and specially detained had their own ‘colour’. This document reflects which groups in society were considered dangerous. The degree of danger was determined by the State Security Operational Trio.
Keywords: Soviet occupation; society; repressions; political prisoners; deportees